La Petite Dernière face à la presse française : une réception médiatique fondée sur les nationalismes sexuels - Liza Hammar (Genre, Sexualité et Société)
This article deals with the media reception of La Petite Dernière by Fatima Daas. First, it proposes a discursive analysis, in the light of the critical studies of sexual nationalisms. Then, the analysis focuses on the posture of the author, and the limits imposed on her by the impossibility of the existence of a lesbian, Muslim and proudly banlieusard story. This reception is also compared to other banlieusard writings and other lesbian and LGBTQ+ writings. Finally, La Petite Dernière is analyzed as a novel of spiritual initiation, which makes it all the more inaudible in the French context.